ENHANCING EFL READING COMPREHENSION THROUGH SELF-DIRECTED LEARNING INTEGRATION IN A FLIPPED CLASSROOM ENVIRONMENT: THE MODERATING ROLE OF DIGITAL LITERACY - Satria, Willy (LLDIKTI Wilayah X, 2025)
Objective: This study investigates the effectiveness of integrating Self-Directed Learning (SDL) principles into a Flipped Classroom model to improve English as a Foreign Language (EFL) reading comprehension among undergraduate students. Furthermore, it examines whether students' digital literacy levels moderate this relationship. Methodology: A quasi-experimental 2x2 factorial design was employed involving 60 second-year students from the English Education Study Program at Universitas PGRI Sumatera Barat. Participants were assigned to an experimental group (n=30) taught using a Flipped Classroom model explicitly designed with SDL scaffolding, and a control group (n=30) taught using an A La Carte blended model. The intervention spanned eight weeks. Data were collected using a validated reading comprehension test (based on Barrett’s Taxonomy) and a standardized digital literacy questionnaire, then analyzed using Two-Way ANOVA. Findings: The results revealed a statistically significant main effect for the learning model (p < .05). Students in the Flipped Classroom-SDL group demonstrated superior reading comprehension compared to the A La Carte group. Interestingly, digital literacy did not show a significant main effect or interaction effect, suggesting that the pedagogical structure of SDL effectively supports learners regardless of their technical proficiency. The study concludes that the deliberate integration of SDL strategies, such as goal setting and self-monitoring, within the Flipped Classroom significantly enhances students' ability to comprehend complex EFL texts, overcoming potential barriers posed by low digital literacy.